2019
DOI: 10.3390/ph12010031
|View full text |Cite
|
Sign up to set email alerts
|

2-Nitroimidazole-Furanoside Derivatives for Hypoxia Imaging—Investigation of Nucleoside Transporter Interaction, 18F-Labeling and Preclinical PET Imaging

Abstract: The benefits of PET imaging of tumor hypoxia in patient management has been demonstrated in many examples and with various tracers over the last years. Although, the optimal hypoxia imaging agent has yet to be found, 2-nitroimidazole (azomycin) sugar derivatives—mimicking nucleosides—have proven their potential with [18F]FAZA ([18F]fluoro-azomycin-α-arabinoside) as a prominent representative in clinical use. Still, for all of these tracers, cellular uptake by passive diffusion is postulated with the disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In relation to the effects seen with IAZA and FAZA treatment on DNA synthesis under hypoxia, it is worth noting that these compounds are structural analogs of nucleosides, and previously FAZA has been reported to bind to human concentrative nucleoside transporters 1–3 (hCNT1-3) [ 55 ]. While our data suggest that such interactions can compete with or block nucleoside transport, evident from a reduction in EdU uptake in response to treatment ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the effects seen with IAZA and FAZA treatment on DNA synthesis under hypoxia, it is worth noting that these compounds are structural analogs of nucleosides, and previously FAZA has been reported to bind to human concentrative nucleoside transporters 1–3 (hCNT1-3) [ 55 ]. While our data suggest that such interactions can compete with or block nucleoside transport, evident from a reduction in EdU uptake in response to treatment ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is not clear if the drugs need to be bioreduced to bind to hCNTs. Maier et al reported binding under normal O 2 conditions (employing Saccharomyces cerevisiae with recombinant hCNTs as their model) [ 55 ], but in FaDu cells, the effects did appear to be hypoxia selective, which suggests that bioreductive activation might play a role in the process. Binding of IAZA and FAZA to nucleoside transporters and subsequent deregulation in the transporters’ activities may provide a potential explanation for the compromised DNA synthesis and slower proliferation rates observed in drug-treated hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, ex vivo biodistribution of β-[ 18 F]17 in mice bearing CT26 colon carcinoma only showed a high uptake in the intestine (indicating rapid clearance) yet a low uptake in other organs and tissues such as blood, liver, kidneys, muscle, and CT26 colon carcinomas. In 2019, Reischl and co-workers described the synthesis of β-2-nitroimidazole-arabinose (β-FAZA) and α-2-nitroimidazole-deoxyribose (α-FAZDR, α-[ 18 F]22) (Figure 11) [137]. Four compounds β-FAZA, FAZA, α-FAZDR and β-FAZDR [131] (Figure 11) were radiofluorinated with 18 F to study the effect of configuration of 2-nitroimidazole pharmacophore and sugar moieties on the detection of hypoxia in tumors.…”
Section: F Radiotracers With Linkers For Hypoxiamentioning
confidence: 99%
“…In vitro cellular uptakes of the four compounds showed a good interaction of β-FAZDR with nucleoside transporters SLC28A3 and SLC28A1, and good interaction of FAZA with nucleoside transporter SLC28A1 whereas α-FAZDR was unable to interact with any transporter and β-FAZA could only inhibit transporters at high concentrations. In vivo PET imaging studies of α-[ 18 In 2019, Reischl and co-workers described the synthesis of β-2-nitroimidazole-arabinose (β-FAZA) and α-2-nitroimidazole-deoxyribose (α-FAZDR, α-[ 18 F]22) (Figure 11) [137]. Four compounds β-FAZA, FAZA, α-FAZDR and β-FAZDR [131] (Figure 11) were radiofluorinated with 18 F to study the effect of configuration of 2-nitroimidazole pharmacophore and sugar moieties on the detection of hypoxia in tumors.…”
Section: F Radiotracers With Linkers For Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation